The role of learners' motivation in MOOC completion. (3rd July 2022) - Semenova, Tatiana
ABSTRACT: Studies have shown that learners' motivation is a significant predictor of the level of engagement in a MOOC. However, the role of motivation in a MOOC's completion remains questionable. In our study, we estimated the role of motivation in a MOOC's completion, controlling for the characteristics of participants and their level of engagement with the course materials. The research database includes the survey and trace data on participants of nine MOOCs related to the economic field, launched on Coursera in 2014–2015. Two research models were created: the first model for all MOOCs' participants; the second model for university-affiliated participants. The results of the logistic regression showed that learners' motivation has a significant relationship with a MOOC's completion. However, not all motives for participation in MOOCs are significantly related to the chances of earning a certificate of completion. Intrinsic motivation, a motive for getting skills that could be useful for changing the workplace, and a motive for earning a certificate significantly increase the chances of a MOOC's completion. In turn, amotivation has a negative relationship with a MOOC's completion.